Semantic Interpretation of Social Network Communities - Maheshwari, Tushar; Reganti, Aishwarya; Kumar, Upendra; Chakraborty, Tanmoy; Das, Amitava (Proceedings of the AAAI Conference on Artificial Intelligence, 2017)
A community in a social network is considered to be a group of nodes densely connected internally and sparsely connected externally.Although previous work intensely studied network topology within a community, its semantic interpretation is hardly understood. In this paper, we attempt to understand whether individuals in a community possess similar Personalities, Values and Ethical background. Finally, we show that Personality and Values models could be used as features to discover more accurate community structure compared to the one obtained from only network information.